A contribution to numerical prediction of surface damage and residual stresses on die-sinking EDM of Ti6Al4V. (August 2021) - Rajhi, Wajdi; Alatawi, Ibrahim; Subhani, Tayyab; Ayadi, Badreddine; Al-Ghamdi, Abdulaziz; Khaliq, Abdul
Abstract: A numerical simulation under plane-strain assumption of residual stresses and damage on titanium alloy Ti6Al4V in die-sinking electrical discharge machining (EDM) process is presented using Johnson–Cook (J–C) model and dynamic explicit temperature-displacement algorithm. A special attention is given to model the damaged thermo-mechanical behavior of EDMed Ti6Al4V alloy while considering the ductile damage evolution via a fully uncoupled damage formulation. A rigorous selection method including analytical and finite-element (FE) computations of tensile fracture behavior with thermal effect is proposed for suitable selection of J–C model parameters for the grade of Ti6Al4V alloy under investigation. The relationships between the machining parameters and both the heat flux density and the available sparking radius are considered for defining sparking analysis input. For a selected set of machining settings, the residual stresses and surface damage profiles were retrieved at the end of a cooling analysis. It has been concluded that J–C constitutive model can be used to describe material damaged thermo-plastic behavior under die-sinking EDM process conditions and thereby forecast temperature distribution, crater cavity shape, thermally induced residual stresses, white layer thickness and EDM thermal cracks formation. Unusually, an approach including damage criterion was proposed for assessment of both the geometry of crater cavity and the thickness of white layer and compared to based-on temperature criterion classical approach. Thus, numerical simulation of damage in die-sinking EDM offers a new insight into the mechanism of surface damage creation and helps to find out such phenomenon very precociously, which is otherwise difficult to access by experiment, such as surface crack formation due to damage mechanism as triggered in sparking phase and which was re-established in cooling. The numerical model yields reliable results for residual stresses profiles when compared with titanium alloy Ti6Al4V experimental results available in literature in the same machining conditions. Graphical abstract: Unlabelled Image